Novel Phenolic Inhibitors of Small/Intermediate-Conductance Ca(2+)-Activated K(+) Channels, KCa3.1 and KCa2.3 - Oliván-Viguera, Aida (Public Library of Science, 2013)
BACKGROUND: KCa3.1 channels are calcium/calmodulin-regulated voltage-independent K(+) channels that produce membrane hyperpolarization and shape Ca(2+)-signaling and thereby physiological functions in epithelia, blood vessels, and white and red blood cells. Up-regulation of KCa3.1 is evident in fibrotic and inflamed tissues and some tumors rendering the channel a potential drug target. In the present study, we searched for novel potent small molecule inhibitors of KCa3.1 by testing a series of 20 selected natural and synthetic (poly)phenols, synthetic benzoic acids, and non-steroidal anti-inflammatory drugs (NSAIDs), with known cytoprotective, anti-inflammatory, and/or cytostatic activities. METHODOLOGY/PRINCIPAL FINDINGS: In electrophysiological experiments, we identified the natural phenols, caffeic acid (EC50 1.3 µM) and resveratrol (EC50 10 µM) as KCa3.1 inhibitors with moderate potency. The phenols, vanillic acid, gallic acid, and hydroxytyrosol had weak or no blocking effects. Out of the NSAIDs, flufenamic acid was moderately potent (EC50 1.6 µM), followed by mesalamine (EC50≥10 µM). The synthetic fluoro-trivanillic ester, 13b ([3,5-bis[(3-fluoro-4-hydroxy-benzoyl)oxymethyl]phenyl]methyl 3-fluoro-4-hydroxy-benzoate), was identified as a potent mixed KCa2/3 channel inhibitor with an EC50 of 19 nM for KCa3.1 and 360 pM for KCa2.3, which affected KCa1.1 and Kv channels only at micromolar concentrations. The KCa3.1/KCa2-activator SKA-31 antagonized the 13b-blockade. In proliferation assays, 13b was not cytotoxic and reduced proliferation of 3T3 fibroblasts as well as caffeic acid. In isometric vessel myography, 13b increased contractions of porcine coronary arteries to serotonin and antagonized endothelium-derived hyperpolarization-mediated vasorelaxation to pharmacological KCa3.1/KCa2.3 activation. CONCLUSIONS/SIGNIFICANCE: We identified the natural phenols, caffeic acid and resveratrol, the NSAID, flufenamic acid, and the polyphenol 13b as novel KCa3.1 inhibitors. The high potency of 13b with pan-activity on KCa3.1/KCa2 channels makes 13b a new pharmacological tool to manipulate inflammation and cancer growth through KCa3.1/KCa2 blockade and a promising template for new drug design.